Запуск синхронных электродвигателей мощностью 8 мВт привода магистральных насосов от параметрического пускового устройства - Барский, Виктор Алексеевич; Башта, Владимир Николаевич; Быканов, Роман Анатольевич; Голубев, Владимир Геннадьевич; Дубров, Николай Николаевич (НТУ "ХПИ", 2010)
Experimental results of starting of 8MW Synchronous Motors for Pump Drives from Parametric Starting Device were obtained and described in the article.
Starting of 8mW synchronous motors for pump drives from parametric starting device
Keywords: энергосбережение; водоснабжение; тариф; ток электрический